Stylasterids (Hydrozoa: Stylasteridae) from Mar del Plata submarine canyon and adjacent area (southwestern Atlantic), with a key to the species off Argentina - Bernal, M.c.; Cairns, S.d.; Penchaszadeh, P.e.; Lauretta, D. (Zootaxa, 2021)
The Argentine continental margin is a poorly explored area as regards its benthic biodiversity. Few works have been made near the Brazil-Malvinas confluence (around 38° S) regarding corals, especially in deep waters (over 1000 m). Hitherto 17 species of stylasterids are known from southwestern Atlantic (SWA) off Argentina. Fourteen species of stylasterids collected from the Mar del Plata submarine canyon and adjacent area in years 2012 and 2013 at depths between 800 and 2200 m are discussed, including the descriptions of 13 of them. The geographic distribution of six species and bathymetric range of occurrence of two species are broadened in this work. Stations where most specimens were collected are located in areas where sedimentation is known to be scarce. Species in common between the study area and the Antarctic region, south of Chile, South Africa, New Zealand and New Caledonia suggest the Circumpolar Antarctic Current and the Malvinas Current are the means for dispersion. A key of identification of all stylasterid species off Argentina is included.